Orchidaceae of Bahia, Brazil: notes on taxonomy and nomenclature - Carvalho, Denis N.; Meneguzzo, Thiago E.c.; Popovkin, Alex; Berg, Cássio Van Den (Phytotaxa, 2016)
In the process of reviewing the relevant literature revision and analysing available botanical specimens for the compilation of a checklist of Orchidaceae for the State of Bahia (Brazil), we identified some taxonomic issues that are dealt with in this paper.